Box-Behnken design optimization of the spray-drying process for yield and antioxidant activity of Koklan remedy extract powder - Apichatwatana, Nutsawadee; Wongwan, Sudaporn; Jongcharoenkamol, Jira; Kriangkrai, Worawut; Rujivipat, Soravoot (Science, Engineering and Health Studies, 2025)
Koklan remedy is a traditional Thai herbal formulation used for the relief of muscle pain and inflammation. However, its decoction form presents limitations, including poor stability and low patient compliance. This study aimed to optimize the extraction and spray-drying conditions to convert Koklan remedy extract into a powder form with high yield and retained antioxidant activity. A Box-Behnken design was employed to investigate the effects of inlet temperature, feed rate, and decoction ratio on powder yield and ABTS radical scavenging activity. The results indicated that all three variables influenced the responses, with decoction ratio emerging as the most significant. The optimum condition for yield was found at inlet temperature, feed rate, and 3.71 decoction ratio. Validation experiments confirmed strong agreement in powder yield prediction but revealed some deviation in antioxidant activity due to model limitations. Overall, this study demonstrates the applicability of response surface methodology for optimizing herbal spray drying processes and supports the development of Koklan remedy powder as a more stable, scalable, and patient-friendly dosage form.